Effect of CaO/MgO ratio on the optical and theoretical parameters of alumino‐borosilicate glasses. (19th September 2018) - Kaur, Mandeep; Kaur, Gurbinder; Pandey, Om Prakash; Kumar, Vishal
Abstract: Glass series (10+ x )CaO–(10− x )MgO–10SrO–10B2 O3 –20Al2 O3 –40SiO2 ( x = 0, 2.5, 5, 7.5) has been prepared by melt quenching technique. Influence of CaO/MgO ( R ) ratio on the properties like density/molar volume has been investigated and correlation has been established between them. The theoretical parameters like electronegativity of metal ion/oxide ion, ionic concentration, interionic distance, optical basicity, and polarizability have also been obtained. The optical properties such as band gap, Urbach energy, and band positions of pristine as well as heat‐treated glasses have been studied using UV‐visible and Fourier transform infrared spectroscopy (FTIR), respectively. Electron paramagnetic resonance (EPR) spectra are obtained to find the values of spin Hamiltonian parameters ( g values) for all the glass samples. It could be observed that with the increase in CaO content or R ratio, heat‐treated glasses exhibit direct band gap within 5.92‐6.01 eV range. The Urbach energy lies within the 0.62‐0.86 eV range for all the heat‐treated glass samples. Abstract : In this article effect of CaO/MgO ratio on optical and theoretical parameters of alumino‐borosilicate glasses has been investigated. The band gap, Urbach energy, and band positions of pristine as well as heat treated glasses have also been analyzed with varying CaO/MgO ratio using UV‐visible and Fourier transform infrared spectroscopy (FTIR), respectively. Furthermore, electron paramagnetic resonance spectra are obtained to evaluate g values for all the glass samples.